Disease burden of tuberculosis and post-tuberculosis in Inner Mongolia, China, 2016–2018 — based on the disease burden of post-TB caused by COPD - Caimei Jing; Huiqiu Zheng; Xuemei Wang; Yanling Wang; Yifan Zhao; Sijia Liu; Jing Zhao; Qianqian Du (BMC Infectious Diseases, 2023)
Abstract Background Tuberculosis (TB) remains one of the most serious infectious diseases worldwide. China has the second highest TB burden globally, but existing studies have mostly neglected the post-tuberculosis (post-TB) disease burden. This study estimated the disease burden of TB and post-TB in Inner Mongolia, China, from 2016 to 2018. Methods Population data were collected from TB Information Management System. Post-TB disease burden was defined as the burden caused by Chronic Obstructive Pulmonary Disease (COPD) occurring after patients with TB were cured. To estimate the incidence rate of TB, standardized mortality rate, life expectancy, and cause eliminated life expectancy, using descriptive epidemiological, abridged life table and cause eliminated life table. On this basis, the Disability-Adjusted Life Years (DALY), Years Lived with Disability (YLD) and Years of Life Lost (YLL) due to TB were further be estimated. The data were analyzed using Excel 2016 and SPSS 26.0. Joinpoint regression models were used to estimate the time and age trends of the disease burden of TB and post-TB. Results The TB incidence in 2016, 2017, and 2018 was 41.65, 44.30, and 55.63/100,000, respectively. The standardized mortality in the same period was 0.58, 0.65, and 1.08/100,000, respectively. From 2016 to 2018, the total DALYs of TB and post-TB were 5923.33, 6258.03, and 8194.38 person-years, and the DALYs of post-TB from 2016 to 2018 were 1555.89, 1663.33, and 2042.43 person-years. Joinpoint regression showed that the DALYs rate increased yearly from 2016 to 2018, and the rate of males was higher than that of females. TB and post-TB DALYs rates showed a rising tendency with increasing age (AAPC values were 149.6% and 157.0%, respectively, P < 0.05), which was higher in the working-age population and elderly. Conclusion The disease burden of TB and post-TB was heavy and increased year by year in Inner Mongolia from 2016 to 2018. Compared with the youngster and females, working-age population and the elderly and males had a higher disease burden. Policymakers should be paid more attention to the patients’ sustained lung injury after TB cured. There is a pressing need to identify more effective measures for reducing the burden of TB and post-TB of people, to improve their health and well-being.